Additive Value of Preprocedural Computed Tomography Planning Versus Stand‐Alone Transesophageal Echocardiogram Guidance to Left Atrial Appendage Occlusion: Comparison of Real‐World Practice - So, Chak‐yu; Kang, Guson; Villablanca, Pedro A.; Ignatius, Abel; Asghar, Saleha; Dhillon, Dilshan; Lee, James C.; Khan, Arfaat; Singh, Gurjit; Frisoli, Tiberio M.; O’Neill, Brian P.; Eng, Marvin H.; et al. (Journal of the American Heart Association, 2021)
Background Transesophageal echocardiogram is currently the standard preprocedural imaging for left atrial appendage occlusion. This study aimed to assess the additive value of preprocedural computed tomography (CT) planning versus stand-alone transesophageal echocardiogram imaging guidance to left atrial appendage occlusion. Methods and Results We retrospectively reviewed 485 Watchman implantations at a single center to compare the outcomes of using additional CT preprocedural planning (n=328, 67.6%) versus stand-alone transesophageal echocardiogram guidance (n=157, 32.4%) for left atrial appendage occlusion. The primary end point was the rate of successful device implantation without major peri-device leak (>5 mm). Secondary end points included major adverse events, total procedural time, delivery sheath and devices used, risk of major peri-device leak and device-related thrombus at follow-up imaging. A single/anterior-curve delivery sheath was used more commonly in those who underwent CT imaging (35.9% versus 18.8%; <0.001). Additional preprocedural CT planning was associated with a significantly higher successful device implantation rate (98.5% versus 94.9%; =0.02), a shorter procedural time (median, 45.5 minutes versus 51.0 minutes; =0.03) and a less frequent change of device size (5.6% versus 12.1%; =0.01), particularly device upsize (4% versus 9.4%; =0.02). However, there was no significant difference in the risk of major adverse events (2.1% versus 1.9%; =0.87). Only 1 significant peri-device leak (0.2%) and 5 device-related thrombi were detected in follow-up (1.2%) with no intergroup difference. Conclusions Additional preprocedural planning using CT in Watchman implantation was associated with a higher successful device implantation rate, a shorter total procedural time, and a less frequent change of device sizes.